PENGGUNAAN INTERNET DAN PELUANG BERWIRAUSAHA DI INDONESIA - Andi Alimuddin (Jurnal Kewirausahaan dan Bisnis, 2021)
Currently, the internet is a necessity in social and economic life which provides convenience in communication and social interaction. In addition, the presence of the internet, which is supported by advances in digital technology, is expected to provide business opportunities. Internet access has become easier with the rapid use of cellular telephones. This study aims to examine the effect of internet use on entrepreneurial opportunities in Indonesia through descriptive analysis and binary logistic regression approaches. This research uses data from the 2019 National Socio-Economic Survey. Entrepreneurship in this research is limited to individuals who work assisted by permanent workers or paid workers in the age range of 25 to 44 years. Of the 348735 samples that were the unit of analysis, 7108 were entrepreneurs or about 2.04 percent. This study found that individuals who use the internet have a higher chance of becoming an entrepreneur than individuals who do not use the internet and this finding is statistically significant. In addition, the level of education significantly affects individuals to become entrepreneurs, but individuals with higher education have a lower tendency to become entrepreneurs than those with high school education and below.Keywords: Binary Logistic Regression, Entrepreneurship, Internet